Resistance of Aphids (Aphis gossypii) to Synthetic Insecticides: A Case Study in Taktakan and Walantaka District, Serang City - Wina Lestari, Wina Lestari; Rumbiak, Julio Eiffelt Rossafelt; Romdhonah, Yayu; Saylendra, Andree (Jurnal Agroekoteknologi Terapan, 2025)
This study aimed to determine the level of resistance of aphids to synthetic insecticides that have active ingredients of Carbamate, Organophosphate, Pyrethroid, Neonicotinoid, and Flupyradifurone in Serang City, Banten Province. Aphid pest samples were obtained from Taktakan District (Kalang Anyar and Pancur Villages) and Walantaka District (Pager Agung and Kiara Villages) in Serang City. The parameters observed were the morphology of aphids and the resistance of aphids, by observing 72 hours after the application of synthetic insecticides. The results of the study showed that the level of resistance of aphids to synthetic insecticides that experienced potential resistance at LC50 was Flupyradifurone and Carbamate in Taktakan and Walantaka Districts. There was a significant effect of the time needed to kill 50% of the number of test insects in Taktakan District, which was 31.038 hours, and Walantaka District was 29.415 hours. Keywords: Aphids gossypii, Insecticide, Morphology, Lethal Concentration, Lethal Time, Resistance